Counter charge cluster formation in molecular doping of molybdenum disulfide - Lee, Jonghoon; Kedziora, Gary; Glavin, Nicholas; Roy, Ajit K. (Frontiers in Carbon, 2023)
Molybdenum disulfide (MoS2) gas sensor prototypes report orders of magnitude higher sensitivity towards nitrogen dioxide (NO2) over ammonia (NH3). Based on the cluster formation model and density functional theory calculation of charge transfer, NO2 is found to form a tightly bound cluster of counter charge upon carrier donation. On the other hand, NH3 forms only a semi-localized cluster of counter charge over wide area of MoS2, rendering larger collision cross section of Coulomb interaction between the charge carrier and the counter charge. We report the localization of counter charge cluster as a measure potentially affecting molecular doping efficiency.